Ang mabahong prutas - Ordinario, Mary Ann; Royong, Rolando Nolasto II (Plaridel St., Kidapawan City, Philippines ABC Educational Development Center, 2018)
Durian, the King of Fruits, is also infamous for its spiky skin and very strong odor. Legend has it the durian originally had smooth skin and smelled like freshly bloomed flowers on a sunny day. What could possibly have happened for it to change so drastically?--Pumplepie: books and happiness.
"Setyembre 2018"
"Second prize winner [of the] Samsung KidsTime Author's Award : 2016 AFCC Singapore."--Cover.
Keywords: Durian -- Philippines -- Legends -- Juvenile literature; Children's stories, Filipino